2015
DOI: 10.1080/09205063.2014.994948
|View full text |Cite
|
Sign up to set email alerts
|

About the effect of eye blinking on drug release from pHEMA-based hydrogels: anin vitrostudy

Abstract: Abstract:The development of new ophthalmic drug delivery systems capable of increasing the residence time of drugs in the eye and improve its bioavailability relatively to eyedrops has been object of intense research in recent years. Several studies have shown that drug loaded therapeutic soft contact lenses (SCLs) constitute a promising approach, with several potential advantages as compared with collyria. The main objective of this work is to study the effect of repetitive load and friction cycles caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 51 publications
2
9
0
1
Order By: Relevance
“…In a previous work performed by Serro et al, the authors concluded that friction does not influence significantly the LVF release of thermal polymerized HEMA/PVP hydrogels, which is confirmed by the data presented here.…”
Section: Resultssupporting
confidence: 90%
“…In a previous work performed by Serro et al, the authors concluded that friction does not influence significantly the LVF release of thermal polymerized HEMA/PVP hydrogels, which is confirmed by the data presented here.…”
Section: Resultssupporting
confidence: 90%
“…This observation also has been reported in another study modelling the effects of blinking on drug release from hydrogels. 24 Furthermore, the tear film is shear-thinning (non-Newtonian) in which the viscosity is not constant. We speculate that the rubbing process between the eyelid and corneal eyepiece decreases the viscosity of the ATS, 33,39 which increases the amount of drugs released from the CL.…”
Section: Discussionmentioning
confidence: 99%
“…23 The effects of eye blinking on drug release from hydrogels has been noted in only one study. 24 To our knowledge, no studies have examined the combined effects of an artificial tear solution (ATS) that mimics the composition of the human tear film and mechanical wear on drug release from CLs. The aim of this study was to evaluate and compare the release of moxifloxacin from a variety of daily disposable (DD) CLs in an ATS when exposed to mechanical rubbing using a novel in vitro eye model.…”
Section: Introductionmentioning
confidence: 99%
“…The predicted drug concentrations were estimated from the theoretical fractional mass release profiles based on a mathematical model described in Paradiso el al. [5]. Here, the thickness of the inner loaded lens was maintained at 0.5 mm, and the drug diffusivity in that material was maintained at 7.5x10 -13 m 2 s -1 .…”
Section: Resultsmentioning
confidence: 99%
“…The main drawbacks that remain to be solved include the initial burst of drug release and the limited duration of active release after the placement of the lens in the eye. The simplest approach for preparing drug-loaded OLs, which has been the focus of many previous studies, involves soaking hydrophilic lenses in commercial drug solutions [2,5,6]. This minimalistic approach, although leading to more effective drug release control and drug absorption than eye drops, in general, cannot provide extended drug release [7,8].…”
Section: Introductionmentioning
confidence: 99%